Moderate Values Internalization in English Learning at Madrasah Aliyah Level: a Means to Prevent Radicalism - Chubbi Millatina Rokhuma; Rayinda Eva Rahmah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2020)
Moderate values of Tawasuth, Tawazun, and Tasamuh are the values of ASWAJA which means fair, balance, and tolerance. Those values are believed to be able to build the unity of Indonesia. Therefore, those values are appropriate to be revitalized as life guidance in all aspects including educational environment. One of the alternative ways in implementing those values in education is by internalizing them in all learning process, including English learning. This article aims to describe the internalization process of the moderate values of Tawasuth, Tawazun, Tasamuh in the English learning process of some madrasah in Pekalongan regency, especially those which is developed by Ma’arif NU. This study was conducted by using a qualitative approach. The data were collected through an interview, observation, as well as documentation. The research result shows that those values are internalized mostly in the opening activities, especially in the apperception step. In its internalization process, all of the English teachers use transinternal strategy, action and comprehension approach, reflective method, as well as clarification technique. In short, it can be concluded that moderate values can be internalized implicitly in the English learning process through additional explanation in the apperception step. This study contributes to share the idea of the importance of moderate values internalization in English learning process as well as how to internalize them in real context of English learning.